1998
DOI: 10.1097/00002030-199808000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of Pneumocystis carinii pneumonia, bacterial pneumonia and tuberculosis in HIV-infected patients

Abstract: Simple clinical variables, all readily available at the time of hospital admission, can help to differentiate these common pneumonia syndromes in HIV-infected patients. These findings can help to inform clinical decision-making regarding choice of therapy, use of invasive diagnostic procedures, and need for respiratory isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 25 publications
1
41
2
2
Order By: Relevance
“…The chest radiograph typically demonstrates perihilar infiltrates in mild disease and bilateral, symmetrical interstitial infiltrates emanating from the hila in a butterfly pattern in severe disease [69]. Less frequently, PCP may present with unilateral or asymmetrical opacities.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…The chest radiograph typically demonstrates perihilar infiltrates in mild disease and bilateral, symmetrical interstitial infiltrates emanating from the hila in a butterfly pattern in severe disease [69]. Less frequently, PCP may present with unilateral or asymmetrical opacities.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…Although the clinical presentation of pulmonary TB is different to the presentation of pulmonary TB in HIV-1 uninfected patients, the most common symptoms remain cough, fever, night sweats and significant weight loss [Batungwanayo et al, 1992;Bruchfeld et al, 2002]. Relative to HIV-1 uninfected patients, weight loss and fever are more common, whereas haemoptysis is less common and some studies have reported a decreased proportion of patients with cough [Selwyn et al, 1998;Kassu et al, 2007]. Although HIVinfected persons with TB may have the classic symptoms of TB (eg, productive cough, chest pain, shortness of breath, hemoptysis, fever, night sweats, and/or weight loss), many such patients have few symptoms or have symptoms that are even less specific than those mentioned.…”
Section: Clinical Criteriamentioning
confidence: 98%
“…В странах, эндемичных по туберкулезу (РФ отно сится к таким регионам), у больных ВИЧ инфекци ей бактериальную пневмонию наиболее часто при ходится дифференцировать с пневмоцистной пневмонией и туберкулезом, особенно у лиц с под острым началом заболевания [45][46][47].…”
Section: клиническая картина диагностика и прогноз вп у лжвunclassified